Structural, physical and chemical properties of nanostructured nickel-substituted ceria oxides under reducing and oxidizing conditions - Fuentes, Rodolfo Oscar (2016)
This work reports the synthesis of nanostructured Ce1-xNixO2-δ (x = 0.05, 0.1, 0.15 and 0.2) oxides prepared by cation complexation route and with the main objective of studying their redox properties using a combination of electron microscopy, synchrotron radiation X-ray diffraction (SR-XRD) and X-ray absorption near-edge spectroscopy (XANES). The Ce1-xNixO2-δ series of nanopowders maintain the cubic crystal structure (Fm3m space group) of pure ceria, with an average crystallite size of 5-7 nm indicated by XRD patterns and confirmed by transmission electron microscopy. In situ SR-XRD and XANES carried out under reducing (5% H2/He; 5% CO/He) and oxidizing (21%O2/N2) atmospheres at temperatures up to 500 °C show a Ni solubility limit close to 15 at.% in air at room temperature, decreasing to about 10 at.% after exposure to 5% H2/He atmosphere at 500 °C. At room temperature in air, the effect of Ni on the lattice parameter of Ce1-xNixO2-δ is negligible, whereas a marked expansion of the lattice is observed at 500 °C in reducing conditions. This is shown by XANES to be correlated with the reduction of up to 25% of Ce4+ cations to the much larger Ce3+, possibly accompanied by the formation of oxygen vacancies. The redox ability of the Ce4+/Ce3+ couple in nanocrystalline Ni-doped ceria is greatly enhanced in comparison to pure ceria or achieved by using other dopants (e.g. Gd, Tb or Pr), where it is limited to less than 5% of Ce cations.